2008
DOI: 10.1088/1475-7516/2008/10/018
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray nuclei, antiprotons and gamma rays in the galaxy: a new diffusion model

Abstract: We model the transport of cosmic ray nuclei in the Galaxy by means of a new numerical code. Differently from previous numerical models we account for a generic spatial distribution of the diffusion coefficient. We found that in the case of radially uniform diffusion, the main secondary/primary ratios (B/C, N/O and sub-Fe/Fe) and the modulated antiproton spectrum match consistently the available observations. Convection and re-acceleration do not seem to be required in the energy range we consider: 1 ≤ E ≤ 10 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
321
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 317 publications
(327 citation statements)
references
References 59 publications
6
321
0
Order By: Relevance
“…Such smooth variation was incorporated in our second model, which assumed an exponentially growing diffusion coefficient, which has been shown to produce consistent fits to conventional astrophysical cosmic ray observables in Ref. [4]. We found numerical solutions as well as analytic approximations valid at high antiproton energies for this model.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Such smooth variation was incorporated in our second model, which assumed an exponentially growing diffusion coefficient, which has been shown to produce consistent fits to conventional astrophysical cosmic ray observables in Ref. [4]. We found numerical solutions as well as analytic approximations valid at high antiproton energies for this model.…”
Section: Discussionmentioning
confidence: 58%
“…[4]. Using this code, it was demonstrated that a consistent fit to observed cosmic ray isotope ratios can be obtained in this model.…”
Section: Exponentially Increasing Diffusion Coefficientmentioning
confidence: 82%
See 3 more Smart Citations